PERAN ARKEOLOGI PUBLIK DALAM PELESTARIAN KAWASAN BOROBUDUR SEBAGAI KAWASAN STRATEGIS NASIONAL (KSN) - , Wiwt Kasiyati, S.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Borobudur Temple has been enlisted as World Cultural Heritage by UNESCO, so it has to be preserved. The efforts in preserving Borobudur area actually has been conducted in 1979 as JICA composed a master plan. In that master plan, Borobudur is divided into 5 zones, in which different institutions manage the zones. Over time there have been inconsistencies in the implementation of the management for Zone 1, 2, 3, 4 and 5 that raise several problems, such as Borobudur area is less sustainable, Borobudur community is less prosperous, and community involvement is lacking in the preservation of Borobudur area. The problems have caught UNESCOâs attention until World Heritage Committee recommends the government of Indonesia to review Presidential Decree No. 1 Year 1992 with the hope to improve the quality of Borobudur area management. The Indonesian government then follows the recommendation by revising the spatial zoning and designates Borobudur area as a National Strategic Area. With regards to that matter, this study is focused to find out the role of community in the preservation of Borobudur Temple, because public archaeology places the community as protector and conservator of the area, to know the understanding of the community regarding Borobudur area as a National Strategic Area, and to find out public presentation policy to regulate Borobudur area as a National Strategic Area as well as Borobudur community development. The method of the study uses public archaeology approach as well as the approach that is oriented into community through community participation and empowerment. The stages of the study are data collection (field observation in the land use change and study on community), data analysis, and synthesis of data. The result shows that in public archaeology the community is positioned as the protector and conservator of the site, but in truth the participation of the community in preserving Borobudur Temple and its surrounding area is not yet optimal. According to the community, participation in preserving Borobudur Temple means that they involve in the maintenance of the temple. In addition, the community has not fully aware that the area would be designated as a National Strategic Area as a result of lack of information and public archaeologyâs role as information media. The information should be delivered as a government policy through public information of Borobudur National Strategic Area so that the community would have better understanding.